Correlation between ASTA units-carotenoid concentration in paprika. Prediction of the color stability during storage - Antonio Pérez-Gálvez; Mª Isabel Mínguez-Mosquera; Juan Garrido-Fernández; Mª Mercedes Lozano-Ruiz; Vicente Montero-de-Espinosa (Grasas y Aceites, 2004)
Paprika obtained through the traditional process, from fruits dried in oak ovens, is stored at room temperature for 18 months. Samples are taken at 2-3 months time intervals and color quantity is evaluated, measuring it as ASTA units and carotenoid content. Values obtained from both measurements are compared, achieving a good correlation between ASTA units and total carotenoid content. As a result two equations are proposed, one linking both parameters and another which predicts the remaining ASTA unit as a function of storage time. ASTA values after 18 months of storing time are ca. 55 % of the initial values.